Effects of varying EGR rates on the nitric oxide (NOx) emissions - Wasiu, Saheed; Sulaiman, S. A. (2010)
Exhaust gas recirculation (EGR) is one of the principal techniques used to control spark ignition NOX. A fraction of the exhaust gas is recycled through a control valve from the exhaust to the engine intake system. However, EGR has different effect on performance, combustion, and emissions production that are difficult to distinguish (increase of intake temperature, delay of rate of heat release (ROHR), decrease of peak heat release, decrease in oxygen concentration (and thus of global air/fuel ratio (AFR) and flame temperature) etc and thus the impact of EGR on NOX is not perfectly understood; especially under high EGR rates. An experimental study has been conducted to study various effects of EGR rates on nitric oxide emission (NO) of the direct injection compressed natural gas engine at various rious excess air ratios ( 0.9 = גּ , 1.0, 1.1 and 1.2). The results showed that as the EGR is increased; nitric oxide emissions (NO) reduced drastically at various fraction of EGR. Nitric oxide emissions (NO) emission shows its highest value at excess air ratio of 1.1 (slightly lean) for natural gas-EGR engine because the oxygen concentration at slightly lean mixture results in a higher nitric oxide emissions (NO) concentration when compared with that at stoichoimetric equivalence ratio. More so, at stoichiometric mixture the amount of NO emission released at both 0% and 60% EGR rates are 220 ppm/Kw and 100 ppm/kW respectively. This shows that NO emission under wide-open-throttle (WOT) and stoichiometric condition was about 50% lower than that under normal condition without EGR (0%). Moreover, EGR addition equally reduces cylinder gas temperature and pressure. It can thus be concluded that NO emission concentration is strongly influenced by excess air ratio while it is difficult to realize stable combustion at high temperature.